Cohomological approach to reflexive graphs - Ege, Ozgur; Karaca, Ismet (Utilitas Mathematica, 2022)
In this paper, we construct a cohomology structure for reflexive graphs. We also prove the Universal coefficient theorem for singular cohomology in graphs. We show that the Kiinneth theorem doesn't yield for graphs. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.